2007
DOI: 10.1097/gim.0b013e31802d74de
|View full text |Cite|
|
Sign up to set email alerts
|

Whole blood RNA offers a rapid, comprehensive approach to genetic diagnosis of cardiovascular diseases

Abstract: Purpose: Long QT Syndrome, Marfan Syndrome, hypertrophic and dilated cardiomyopathy are caused by mutations in large, multi-exon genes that are principally expressed in cardiovascular tissues. Genetic testing for these disorders is labor-intensive and expensive. We sought to develop a more rapid, comprehensive, and cost-effective approach.Methods: Paired whole blood samples were collected into tubes with or without an RNA-preserving solution, and harvested for whole blood RNA or leukocyte DNA, respectively. La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 47 publications
(57 reference statements)
1
17
0
1
Order By: Relevance
“…Identification of a novel pseudoexon mutation in FBN1 confirms a role of cryptic mutations leading to the condition. In addition, these results suggest that analysis of the FBN1 message should be considered when the standard genetic diagnosis fails to identify a mutation (Miller et al 2007). Only a few cases of pseudoexon mutations have been reported to cause human genetic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of a novel pseudoexon mutation in FBN1 confirms a role of cryptic mutations leading to the condition. In addition, these results suggest that analysis of the FBN1 message should be considered when the standard genetic diagnosis fails to identify a mutation (Miller et al 2007). Only a few cases of pseudoexon mutations have been reported to cause human genetic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, Miller et al [31] decided to establish peripheral whole blood to be a suitable material for isolation of mRNA for genetic testing use in the diagnosis of certain diseases of the cardiovascular system, including LQTS. Their innovative results showed that the expression profile of genes, of which mutations are responsible for the occurrence of LQTS, can be successfully examined with the use of mRNA isolated from peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…50 mL of blood), skin biopsy, or fibroblasts culture. In addition, there was another limitation to the use of mRNA in the diagnosis of LQTS, namely, the fact that the expression of genes related to the occurrence of this disease is strictly limited to the myocardial cells and that mRNA transcripts could not be successfully extracted from lymphocytes or fibroblasts culture [31, 32]. …”
Section: Discussionmentioning
confidence: 99%
“…Although a number of genetic targets associated with prolonged QTc intervals have been identified and studied, the utility of this information in perioperative risk reduction is limited [20][21][22][23][24]. Recently, Arking et al reported that the gene, NOS1AP (CAPON), coding for a regulator of neuronal nitric oxide synthase, constitutes a new genomic target that modulates cardiac repolarization [25].…”
Section: Introductionmentioning
confidence: 99%